Connexin Signaling in the Juxtaglomerular Apparatus (JGA) of Developing, Postnatal Healthy and Nephrotic Human Kidneys - Kosovic, Ivona (Int J Mol Sci, 2020)
Our study analyzed the expression pattern of different connexins (Cxs) and renin positive cells in the juxtaglomerular apparatus (JGA) of developing, postnatal healthy human kidneys and in nephrotic syndrome of the Finnish type (CNF), by using double immunofluorescence, electron microscopy and statistical measuring. The JGA contained several cell types connected by Cxs, and consisting of macula densa, extraglomerular mesangium (EM) and juxtaglomerular cells (JC), which release renin involved in renin-angiotensin- aldosteron system (RAS) of arterial blood pressure control. During JGA development, strong Cx40 expression gradually decreased, while expression of Cx37, Cx43 and Cx45 increased, postnatally showing more equalized expression patterning. In parallel, initially dispersed renin cells localized to JGA, and greatly increased expression in postnatal kidneys. In CNF kidneys, increased levels of Cx43, Cx37 and Cx45 co-localized with accumulations of renin cells in JGA. Additionally, they reappeared in extraglomerular mesangial cells, indicating association between return to embryonic Cxs patterning and pathologically changed kidney tissue. Based on the described Cxs and renin expression patterning, we suggest involvement of Cx40 primarily in the formation of JGA in developing kidneys, while Cx37, Cx43 and Cx45 might participate in JGA signal transfer important for postnatal maintenance of kidney function and blood pressure control.